2000
DOI: 10.1291/hypres.23.377
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hypertensive Left Ventricular Hypertrophy and Levels of Endothelin and Nitric Oxide.

Abstract: To investigate the relationship between hypertensive left ventricular hypertrophy (LVH) and levels of endothelin (ET) and nitric oxide (NO), and to provide an experimental basis for prevention and treatment of hypertensive LVH. Fifty eight hypertensive patients and 14 healthy controls were studied. All patients were examined by echocardiography. Left ventricular mass (LVM) and left ventricular mass index (LVMI) were calculated using Devereux RB formula. Hypertensive patients were divided into a LVH (+) group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
2
16
2
Order By: Relevance
“…Increased plasma levels of ETs are positively correlated with severity of LVH in humans (15). There are conflicting data, however, regarding whether plasma ET-1 levels are elevated in SHRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased plasma levels of ETs are positively correlated with severity of LVH in humans (15). There are conflicting data, however, regarding whether plasma ET-1 levels are elevated in SHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma levels of ET-1 occur during hypertension and heart failure and correlate with severity of LVH (15). ET receptor antagonists attenuate LVH in some experimental models in vivo (17,20).…”
mentioning
confidence: 99%
“…NO levels are reduced in the plasma of hypertensive patients with left ventricular hypertrophy (LVH) [7]. NOdeficient hypertension induced by treatment of rats with the NOS inhibitor, N G -nitro-L-arginine methyl ester (L-NAME) is characterised in myocardium by hypertrophy, fibrosis, ischemia and necrosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gα13 regulates Na/H exchanger activity (7,8), extracellular signal regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK) (9 -11), nuclear factor κB (NF-κB) (12) and the activity of the low molecular weight GTPase, Rho (13 -15), and is also capable of neoplastic transformation, induction of apoptosis, and stimulation of actin reprotein kinases (ERK, JNK, and p38) (23,24). Because of its vasoconstrictor and growth-promoting action, numerous studies indicate that ET-1 is involved in the pathogenesis of a broad spectrum of renal and cardiovascular diseases (21,22,(25)(26)(27). Previous studies have demonstrated that ET-1 induced ET-1 production through ETAR and/or ETBR-mediated pathways, suggesting that a sustained ET-1 autocrine loop contributes to the progression of cardiovascular and renal diseases (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%